The Long-Term Effects of the Deepwater Horizon Oil Spill on Women's Depression and Mental Distress. (15th February 2018) - Rung, Ariane Lisann; Oral, Evrim; Fontham, Elizabeth; Harrington, Daniel J.; Trapido, Edward J.; Peters, Edward S.
Abstract: Objective: The purpose of the study is to describe changes in mental health among women following an oil spill and to examine their association with the Deepwater Horizon oil spill (DHOS). Methods: The Women and Their Children's Health study followed 2038 women in Louisiana after the DHOS. Subjects were interviewed in 2012-2014 and 2014-2016. Oil spill exposure was characterized using survey items about economic and physical exposures. Outcomes were depressive symptoms and mental distress. Results: After adjustment for relevant demographics, depressive symptoms increased over 2 time points following the DHOS, whereas symptoms of mental distress decreased. For every year increase in time since the DHOS, the rate ratio for depressive symptoms increased by a factor of 1.08. In contrast, the rate ratio for mental distress decreased by a factor of 0.97. In addition, initial associations between economic and physical exposure to the DHOS persisted up to 6 years after the spill; women who were more highly exposed experienced higher levels of depressive symptoms (rate ratios ranged from 1.08 to 1.11) and mental distress (rate ratios from 1.05 to 1.11) at each time point than women who were less exposed. Conclusion: A better understanding of recovery patterns following an oil spill can help direct critical mental health response efforts. ( Disaster Med Public Health Preparedness . 2019;13:183–190)